Pratica della Gentilezza: l' intervento gestaltico integrato sul fenomeno del bullismo - Milena Mazzara, Lorena Perrone, Sebastiana Cipponeri, Letizia Cacciabaudo, Angela Ciulla, Salvatore Renda (Marp Edizioni, 2021)
Bullying involves many preteens, engraving, sometimes to a considerable extent, on their personal serenity and balance on their relationship. It is a phenomenon that cannot be reduced to the overbearing behavior of a single boy, but has a multidimensional configuration, that involves the whole group in which it occurs, characterized mainly by prevarication dynamics. There are several anti-bullying programs put into action, but none of them uses the integrated Gestalt approach, which I believe may be a significant orientation both for reading the phenomenon and for the intervention of the intra-group dynamics. The postulate is to create a methodological group device that affects the phenomenon, through several specific steps, with the transversal objective of enhancing in all partecipants awareness, responsibility, empathy and self-efficacy. The different steps of intervention are conducted within the relational field, at the border - contact I-you, in which the individual experiences a totality of coexisting phenomena that interact and influence each other: the experiences. Mind-body experience is the knowledge foundation and passes through the different levels of experience. The contact cycle will mark the process's explication times, both inside the specific meeting (intra-cycle), and in the entire path (inter-cycle), in a continuous sequence of backgrounds and figures.